Transitioning in state care: a phenomenological approach to understanding the perceived challenges of transitions for older youth in foster care - Washington, Marcellis D. (Kansas State University, 2023)
I explored the experiences of former foster youth (FFY) as they transition through the foster care system and navigate high school, aiming to bridge the knowledge gap regarding the lived realities of FFY during these transitions, and emphasizing the challenges they face and the support systems that may be lacking. A qualitative research approach was employed, focusing on the lived experiences of FFY. Data was collected through in-depth, semi-structured interviews with former foster youth and service providers. Additionally, I conducted a document analysis of interagency agreements, protocols, and intervention models. Thematic analysis facilitated the data analysis, helping to discern emergent themes, patterns, and linkages inherent in the collected data. Seven primary themes emerged, highlighting the instability and uncertainty faced by transitioning foster youth. These themes underscored the systemic issues within the foster care system, the reluctance of FFY to form new relationships due to past traumas, and the importance of genuine relationships in guiding them towards positive outcomes. The results also emphasized the barriers FFY face, from disruptions in their educational trajectories to limited access to resources, and their commendable determination to succeed academically. The findings suggest a pressing need for extended care and support for FFY beyond the age of 18. Mentorship programs and support groups are recommended as they offer platforms for FFY to connect with others and reshape their identities. Additionally, there's a call for enhanced interagency collaboration to promote the welfare of youth in foster care and a focus on early intervention strategies to prevent the need for foster care placements.
Keywords: Foster youth